Amyloid‐β efflux from the central nervous system into the plasma. Issue 6 (24th October 2014) - Roberts, Kaleigh Filisa; Elbert, Donald L.; Kasten, Tom P.; Patterson, Bruce W.; Sigurdson, Wendy C.; Connors, Rose E.; Ovod, Vitaliy; Munsell, Ling Y.; Mawuenyega, Kwasi G.; Miller‐Thomas, Michelle M.; Moran, Christopher J.; Cross, Dewitte T.; et al.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to measure the flux of amyloid‐β (Aβ) across the human cerebral capillary bed to determine whether transport into the blood is a significant mechanism of clearance for Aβ produced in the central nervous system (CNS). Methods Time‐matched blood samples were simultaneously collected from a cerebral vein (including the sigmoid sinus, inferior petrosal sinus, and the internal jugular vein), femoral vein, and radial artery of patients undergoing inferior petrosal sinus sampling. For each plasma sample, Aβ concentration was assessed by 3 assays, and the venous to arterial Aβ concentration ratios were determined. Results Aβ concentration was increased by ∼7.5% in venous blood leaving the CNS capillary bed compared to arterial blood, indicating efflux from the CNS into the peripheral blood (p < 0.0001). There was no difference in peripheral venous Aβ concentration compared to arterial blood concentration. Interpretation Our results are consistent with clearance of CNS‐derived Aβ into the venous blood supply with no increase from a peripheral capillary bed. Modeling these results suggests that direct transport of Aβ across the blood–brain barrier accounts for ∼25% of Aβ clearance, and reabsorption of cerebrospinal fluid Aβ accounts for ∼25% of the total CNS Aβ clearance in humans. Ann Neurol 2014;76:837–844